1997
DOI: 10.1080/00103629709369820
|View full text |Cite
|
Sign up to set email alerts
|

Effect of corncob compost on plant growth in an acid red soil

Abstract: A comparison of corncob compost with lime on plant growth was studied in acid red soil with pH of 4.07. Lettuce, pea, and corn were selected as test plants for their varying tolerance to acid soil. The pot experiment compared six soil treatments and a check. Soil amendments were 1, 2, and 4 cmol calcium carbonate (CaCO 3 ) kg -1 and 5, 10, and 20 g corncob compost kg -1 soil. Results showed higher manganese (Mn) than aluminum (Al) content of the shoot in all check group plants. Reduced shoot Mn content increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…As respostas positivas da alface à calagem evidenciam a suscetibilidade da espécie à acidez do solo e, portanto, à necessidade da adoção dessa prática para aumentar a produtividade (Hemphill & Jackson, 1982;Trani et al, 1996;Chung & Wu, 1997). Por outro lado, Nicoulaud et al (1990) não constataram resposta da alface quando cultivada em condições de acidez do solo (pH, 5,4; Ca, 23 mmol c dm -3 e Mg, 14 mmol c dm -3 ).…”
Section: Resultsunclassified
“…As respostas positivas da alface à calagem evidenciam a suscetibilidade da espécie à acidez do solo e, portanto, à necessidade da adoção dessa prática para aumentar a produtividade (Hemphill & Jackson, 1982;Trani et al, 1996;Chung & Wu, 1997). Por outro lado, Nicoulaud et al (1990) não constataram resposta da alface quando cultivada em condições de acidez do solo (pH, 5,4; Ca, 23 mmol c dm -3 e Mg, 14 mmol c dm -3 ).…”
Section: Resultsunclassified
“…For the ratio of bentonite, charcoal, and corncob to add to sandy soil, we established 4% as being suitable because the literature showed positive effects at this ratio [26,28,38]. In July 2013, we prepared 7 kg each of bentonite and charcoal (made from Acacia sp.)…”
Section: Preparation Of Materials Soil and Teak Seedlingsmentioning
confidence: 99%
“…The P accumulation of composttreated plants was higher than for those receiving the CHEM treatment. Chung and Wu (1997) and Hue (1991) indicated that organic matter increased the availability of soil phosphate. The activity of organic matter in making soil phosphate available has been attributed to the ability of certain metabolic products, of microbiological decomposition, to form stable complex molecules with the iron and aluminum responsible for phosphate fixation in acid soils.…”
Section: Discussionmentioning
confidence: 99%